1994
DOI: 10.1007/bf01467919
|View full text |Cite
|
Sign up to set email alerts
|

Early development of patella infera after knee fractures

Abstract: The condition referred to as patella infera is characterized by a permanent shortening of the patellar ligament and is associated with a severely limited range of motion of the knee joint. Patella infera is a common complication of injury or surgery to the knee joint, and it is generally considered a condition that presents after a variable, albeit considerable time after injury. A review of the knee roentgenograms of patients with arthrofibrosis and patella infera showed this condition to be an immediate comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 5 publications
0
31
0
Order By: Relevance
“…4). Floren et al 5 found an incidence of 37% patella infera after a standard TKA as compared with 12% after a MIS-TKA in which the patella was not everted and only partial excision of the fat pad was done. This reduced incidence of patella infera after a less invasive approach, in which the patella is only displaced and not everted, was also associated with a better functional outcome, less pain, and better range of motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Floren et al 5 found an incidence of 37% patella infera after a standard TKA as compared with 12% after a MIS-TKA in which the patella was not everted and only partial excision of the fat pad was done. This reduced incidence of patella infera after a less invasive approach, in which the patella is only displaced and not everted, was also associated with a better functional outcome, less pain, and better range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Patella infera after TKA has been reported in 10%65% of cases and has been linked to patellar eversion, radical excision of the fat pad, and lateral release. 5,6 In a prospective randomized controlled trial of 84 patients who had either TKA or UKA, 7 Weale et al reported 34% (14 of 41) of the TKA group developed patella infera, defined as 10% or more shortening of the patellar tendon postoperatively, compared with 5% (two of 43) in the UKA group. None of the above studies have reported an effect of fat pad excision on patellar tendon height five years following total knee replacement (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Patella infera may occur after knee fractures, 25 high tibial osteotomy, 28 reconstruction of the anterior cruciate ligament, 11 and TKA. 19,36 Patella infera is suggested to exist when the Insall-Salvati index has decreased by 10%, Clinical Orthopaedics and Related Research or more.…”
Section: Discussionmentioning
confidence: 99%
“…The tendon is split into 2 halves on the coronal plane equal in width. 6 The lateral half is released proximally from the inferior pole of the patella, detaching the patellar periosteum with an electric scalpel and leaving its insertion at the tibial tuberosity intact. 7…”
Section: Discussionmentioning
confidence: 99%
“…This condition can be either congenital 5 or acquired. The latter can be due to direct patellar trauma, fractures around the knee, 6 a chronic quadriceps tear, 7 paralysis of the quadriceps, quadriceps dysfunction after poliomyelitis, or complex regional pain syndrome. 8,9 Furthermore, this condition can be observed as an iatrogenic consequence of surgical procedures such as osteotomy, 2,3 anterior cruciate ligament reconstruction, or total knee arthroplasty.…”
mentioning
confidence: 99%